Ocena skutecznosi dzialan graczy w zmiennych sytuacjach gry w pilkê siatkowa - Superlak, E.; Wolyniec, J. (Human Movement, 2001)
Volleyball is a team game held in the playing field divided by a net, in which players perform actions with and without a ball (without the possibility to keep the ball), and finishing every action is scored. The essence of competition in every sports game is successful solving present situation whose conditions are generated by the two rival teams (players) whose aims are contradictory. Changeability, diversity and often uniqueness of game situations demand constant readiness for action and permanent decision making from the part of the players. Quickness and accuracy of the decisions made and their successful accomplishing is the condition of efficient actions in the present game situation. In team games solving one situation leads automatically to another situation to solve. Game situations in which a player has relatively favourable and achieving the aim is highly probable are: situation of maximum freedom, complete situation, certain situation. Situations in which action conditions are unfavourable and difficult, and the result is hard to foresee, are: uncertain situation, risky situation, critical situation. Taking as a criterion action accomplishment by a player in respect to the aim and achieved result, we can classify game actions as following: efficient actions, efficient counteractions, inefficient actions, inefficient counteractions, counter-efficient actions, counter-efficient counteractions. Preventing accidental, irrational actions demands the ability of quantitative and qualitative event analysis, knowledge of results obtained earlier as a result of numerous experiences. According to A.V. Carron [1], efficiency of solving situations in a team game is totally determined by mutually relative tasks performed by each player. For the sake of the conducted analysis of discussed phenomenon we classified the players in respect to the results and aims of their actions into: main players, helping players, aiding players. The conditions of harmonious co-operation of players with the main player's actions in a given situation create so-called sequence approach. With this approach towards intentional choice of action variant there emerges the cycle of mutually related decisions, each of which assumes the completion the subsequent phase of the aim. In this way the conditions are created for the decision made by a player as a prior action ("predecessor") to bring about an optimal possibility to act efficiently by the next player ("successor"). In this approach, the sequence of actions in volleyball - when a team possesses the ball - is an action chain, i.e. one or several actions are performed directly one after another when the team possesses the ball. Taking into consideration its logical and content structure and the rules of the game, on the basis of a set of accomplished tasks in a game, the authors distinguished theoretically possible to occur finite set of actions.